Accelerometers for objective evaluation of physical activity following spine surgery. (April 2016) - Rao, Prashanth J.; Phan, Kevin; Maharaj, Monish M.; Pelletier, Matthew H.; Walsh, William R.; Mobbs, Ralph J.
Highlights: This review summarizes evidence on the use of accelerometers for objective physical activity measurement following spine surgery. Data suggests the use of accelerometers following spine surgery patients is a practical and quantitative and objective. The currently available accelerometers may transform the way functional outcomes from spine surgery are assessed. Abstract: With the potential of bias from subjective evaluation scores in spine surgery, there is a need for practical and accurate quantitative methods of analysing patient recovery. In recent years, technologies such as accelerometers and global positioning systems have been introduced as potential objective measures for pain and symptoms following spine surgery. Overall, this perspective article aims to discuss and critique currently utilised methods of monitoring spine surgical outcomes. After analysing current modalities it will briefly analyse new potential methods before examining the place for accelerometers in the field of spine surgery. A literature review was performed on the use of accelerometers for objective evaluation of symptoms and disability after spine surgery, and perspectives are summarised in this article. Physical activity measurement with the use of accelerometers following spine surgery patients is practical and quantitative. The currently available accelerometers have the potential to transform the way functional outcomes from spine surgery are assessed. One key advantage is the collection of standardised objective measurements across studies. Future studies should aim to validate accelerometer data in relation to traditional measures of functional recovery, patient outcomes, and physical activity.